Titanium Phosphate Nanoplates Modified With AgBr@Ag Nanoparticles: A Novel Heterostructured Photocatalyst With Significantly Enhanced Visible Light Responsive Activity - Ren, Manli; Bao, Jiaqiu; Wang, Peifang; Wang, Chao; Ao, Yanhui (Frontiers in Chemistry, 2018)
AgBr@Ag modified titanium phosphate composites were fabricated through a two-step approach. The prepared samples were characterized by X-ray diffraction, scanning electron microscopy and transmission electron microscopy. The optical properties of the composites were characterized using UV-vis diffuse reflectance spectra. The photocatalytic activities of the composites were investigated in the degradation of Rhodamine B and ciprofloxacin under visible light irradiation. AgBr@Ag/titanium phosphate was determined to exhibit considerably higher photocatalytic activity than the corresponding individual components. The mechanism for the enhancement of the photocatalytic activity was determined using photoluminescence spectra and photocurrent measurements. Furthermore, the possible photocatalytic mechanisms of organic compounds degradation were also proposed.